Teknik Bilingual Berbantuan Media Augmented Reality untuk Pengajaran Tahapan Solat bagi Tutor An-Nahl Islamic Preschool & Kindergarten - Sri Wahyuni; Fauzul Etfita; Estika Satriani; Asnawi Asnawi (Smart Education, 2021)
Abstract: An-Nahl Islamic Preschool & Kindergarten is an Islamic-based school and uses a bilingual instruction technique. One of the materials listed in the school curriculum is prayer. Prayer is carried out once a week in the mosque to learn the stages of prayer directly. However, during the COVID-19 pandemic, students could only study and pray at school. Responding to this, the community service team provided a solution by providing teaching materials for the stages of prayer through Bilingual Techniques assisted by Augmented Reality media for An-Nahl Islamic Preschool & Kindergarten Tutors. Activities are carried out directly through strict health protocols. Submission of material is done by direct practice method involving preschool and kindergarten students. According to the time specified, the activity ran smoothly and received good attention and a positive response from tutors and students. Students are directly directed by the tutor to follow the prayer stages by praying in the congregation at school. Keywords: augmented reality; bilingual; media; technique; prayer stagesAbstrak: An-Nahl Islamic Preschool & Kindergarten adalah sekolah berbasis islam dan menggunakan bahasa pengantar yang menggunakan teknik bilingual. Salah satu materi yang tercantum pada kurikulum di sekolah adalah pembelajaran solat. Pembelajaran solat dilakukan satu minggu sekali di masjid agar peserta didik dapat langsung mempelajari tahapan solat. Namun, selama pandemik COVID-19, Peserta didik hanya dapat mempelajari dan melaksanakan solat di sekolah saja. Merespon hal tersebut, tim pengabdian masyarakat memberikan solusi dengan memberikan materi Pengajaran tahapan solat melalui Teknik Bilingual berbantuan media Augmented Reality bagi Tutor An-Nahl Islamic Preschool & Kindergarten. Kegiatan dilaksakan secara langsung melalui protokol kesehatan yang ketat. Penyampaian materi dilakukan dengan metode praktek langsung dengan melibatkan peserta didik yang terdiri dari peserta didik preschool dan kindergarten. Kegiatan berjalan dengan lancar, sesuai dengan waktu yang ditentukan serta mendapat perhatian yang baik serta respon yang positif dari tutor maupun peserta didik. Peserta didik langsung diarahkan oleh tutor mengikuti tahapan solat dengan melakukan solat berjamaah di sekolah. Kata kunci: augmented reality; bilingual; media; teknik; tahapan solat